Aesthetic and philosophical meanings of indigenous Asante Kente - Ayesu, Solomon Marfo (Array, 2021)
Indigenous Ghanaian woven fabrics remain traditional cultural pieces, highlighting the value and heritage of the indigenes in the communities. These fabrics are embedded with historical symbolic connotations that help the people to relate effectively and know their past. Recent studies have identified the tools, materials and new innovations in design by traditional weavers. This study seeks to highlight the aesthetics and philosophical connotations of the indigenous Asante Kente which are highly cherished by the indigenes. As a qualitative research, it adopts the narrative research design to interpret empirical information gathered from master weavers and opinion leaders from two weaving communities (Bonwire and Adanwomase) in the Ashanti Region of Ghana. Information on the indigenous Kente of the Asantes is presented, which draws on the types coupled with their philosophical connotations. The worth of the Asante Kente cloth from both aesthetic and philosophical points of view is also presented in the study. It recommends further studies to promote the artefacts and the Ghanaian culture at large.